القيادة التشاركية وعلاقتها بالإبداع التنظيمي دراسة ميدانية على عيّنة من موظفي إدارة كلية العلوم الاجتماعية والإنسانية - شمسة هناء; عثماني إيمان (University of Eloued جامعة الوادي, 2025)
"تهدف هذه الدارسة إلى معرفة العلاقة بين القيادة التشاركية والإبداع التنظيمي، وقد أجريت الدراسة الميدانية في كلية العلوم الاجتماعية والإنسانية جامعة الشهيد حمة لخضر الوادي على عينة مكونة من 46 موظف إداري من المجتمع الكلي البالغ عددهم 57، حيث تمحورت الدراسة حول إشكالية مفادها هل هناك علاقة بين القيادة التشاركية والإبداع التنظيمي لدى موظفي الإدارة في كلية العلوم الاجتماعية والإنسانية، كما اعتمدت الدراسة على ثلاث فرضيات الا وهي: - هناك علاقة بين تفويض السلطة والابداع التنظيمي داخل الكلية. - هناك علاقة بين المشاركة في اتخاذ القرار والإبداع التنظيمي داخل الكلية. - هناك علاقة بين العمل الجماعي والإبداع التنظيمي داخل الكلية. واعتمدت هذه الدراسة على المنهج الوصفي لأنه الأنسب والأمثل لمعرفة واقع الدراسة وجوانبها ووصفها وتحليلها، بمجتمع قدره 46 مفردة وذلك باستخدام العينة القصدية لمجتمع الدراسة بحيث تم توزيع الاستبيان على مجموع الموظفين الإداريين في الكلية إضافة إلى استخدام المقابلة والملاحظة كأداة تدعيمية وقد تم التوصل إلى نتائج مفادها: ان القيادة التشاركية لها علاقة في تحقيق الابداع التنظيمي، كما ان مشاركة العاملين في القرارات المتعلقة بالعمل تنمي لديهم الشعور بالمسؤولية وتحفز على الابتكار، كذلك تعد بيئة العمل التي تعتمد على فرق جماعية وتفاعلات مستمرة أرض خصبة لتبادل المعرفة وتنمية التفكير الإبداعي. ""This study aims to examine the relationship between participative leadership and organizational innovation. The field study was conducted at the Faculty of Social Sciences and Humanities, University of El Oued, with a sample of 46 administrative staff members out of a total population of 57. The study focused on the central question: Is there a relationship between participative leadership and organizational innovation among administrative staff at the Faculty of Social Sciences and Humanities. The study tested three hypotheses: • there a relationship between delegation of authority and organizational innovation within the faculty. • there a relationship between participation in decision-making and organizational innovation within the faculty. • there a relationship between teamwork and organizational innovation within the faculty. The study adopted a descriptive approach as the most suitable method to understand and analyze the current state of the subject. The sample consisted of 46 individuals selected through purposive sampling. Data was collected using questionnaires distributed to all administrative staff in the faculty, supplemented by interviews and observations. The findings revealed that participative leadership significantly contributes to organizational innovation. Involving employees in work-related decisions fosters a sense of responsibility and stimulates creativity. Additionally, work environments that emphasize teamwork and continuous interaction serve as fertile ground for knowledge exchange and the development of innovative thinking. "
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: الإبداع التنظيمي; العمل الجماعي; المشاركة في اتخاذ القرار; تفويض السلطة; القيادة التشاركية; Participative leadership; delegation of authority; participation in decision-making; teamwork; organizational innovation